The Relationship Leadership and Work Environment with Honorary Employee Satisfaction in The Watcher Office Water Irrigation Area of Seluma - Ida Anggriani; Zahrah Indah Ferina; M. Anggi Andrianto (Journal of Research in Business, Economics, and Education, 2021)
This study aims to determine the relationship between leadership and work environment with honorary employee satisfaction in the watcher office water irrigation area of seluma. The analytical method used to assess leadership and work environment with job honorary employee satisfaction in the watcher office water irrigation area of seluma uses Spearman Rank correlation analysis and t-test and the number of samples in this study were 42 respondents. Based on the results of the study showed that the calculation of Spearman rank correlation between leadership and job satisfaction of honorary employee satisfaction in the watcher office water irrigation area of seluma obtained a value of 0.719 located between the intervals of 0.600 - 0.799, meaning that leadership has a strong relationship with job satisfaction and obtained values tcount 6,543, where tcount > ttable (6,543 > 2,021), which shows that leadership has a significant relationship with honorary employee satisfaction in the watcher office water irrigation area of seluma. While the results of calculations between the work environment with honorary employee satisfaction in the watcher office water irrigation area of seluma obtained a value of 0.930 located between intervals of 0.800 - 0.1000, meaning that the work environment has a very strong relationship with job satisfaction and obtained a tcount of 16.008, where tcount > t table (16.008> 2,021), so it can be concluded that the work environment has a significant relationship with honorary employee satisfaction in the watcher office water irrigation area of seluma.